Organizational Support, Job Resources, Soldiers' Motivational Profiles, Work Engagement, and Affect. Issue 5 (5th June 2017) - Gillet, Nicolas; Becker, Caroline; Lafrenière, Marc-André; Huart, Isabelle; Fouquereau, Evelyne
Abstract : The authors examined the relationships between soldiers' motivational profiles and work correlates. Results showed that the profiles differentially related to perceived organizational support and work engagement in both samples, as well as to communication, supervisor support, and positive and negative affect in Sample 2. Specifically, soldiers with the highest autonomous motivation scores displayed the highest levels of perceived organizational support and work engagement. Moreover, the highest levels of autonomous motivation were associated with the highest levels of communication, supervisor support, and positive affect. Finally, soldiers with low to moderate levels of autonomous motivation reported higher levels of negative affect than those characterized by high autonomous motivation scores. Theoretical and practical implications of the findings are discussed. What is the public significance of this article?: Soldiers with the highest autonomous motivation scores (i.e., those who engage in their professional activities out of pleasure and/or volition and choice) display the highest levels of well-being. These soldiers also perceive the highest levels of organizational support, supervisor support, and communication.